Na-modified nanosheet Au-MOR molecular sieve catalyst as well as preparation method and application thereof
Through the Na-modified nanosheet Au-MOR molecular sieve catalyst, the problem of low methanol yield in methane activation and directional conversion is solved, and the high dispersion and high cycle stability of Au on the catalyst is achieved, thus improving methane activation efficiency and methanol selection are improved. sex.
Patent Information
- Application Number
- CN202411423868.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-12
AI Technical Summary
During the low-temperature activation and directional conversion of methane, the supported molecular sieve catalysts face lower yields of methanol and acetic acid. Building a highly active metal-molecular sieve catalyst to increase the yield of oxygen-containing derivatives is still a key scientific problem that needs to be solved urgently.
Nanosheet Au-MOR molecular sieve catalyst modified with Na is used to regulate the acid center properties of the catalyst through the surface reaction between alkali metal Na and MOR, and highly disperse Au elements in the catalyst to achieve 100% Au atom utilization rate and high efficiency and high methane. Selective catalytic conversion to methanol.
The high dispersion and high cycle stability of Au on the catalyst are achieved, which significantly improves the activation efficiency of methane and the high selectivity of methanol, and the catalyst has a multi-stage pore structure and excellent carbon deposit resistance.
Smart Images

Figure CN119281371A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically relates to a Na-modified nanosheet Au-MOR molecular sieve catalyst, a preparation method thereof, and application thereof in methane oxidation to methanol. Specifically, the catalyst acid center properties and the stabilizing effect on the active metal center Au are regulated by surface reaction of alkali metal Na with MOR, and the catalyst is applied to methane oxidation to methanol reaction. Background Art
[0002] The catalytic conversion of methane to produce high-value-added chemicals is an effective way to efficiently utilize resources such as natural gas and coal. This reaction is known as the "holy grail" reaction in the field of catalysis. The development of new reaction pathways for the efficient oxidation of methane to produce methanol, acetic acid and other compounds using cheap oxygen as an oxidant under mild conditions has always been a hot topic and difficulty in the field of catalysis. Recently, metal-modified molecular sieves, MoS 2 Catalysts such as , Pd-supported phosphomolybdic acid clusters have been reported to react methane with oxygen in an aqueous environment to prepare oxygen-containing compounds at low temperatures (<200°C) or even room temperature, laying a new foundation for this direction [Nat. Catal., 2022, 5, 45.; J. Am. Chem. Soc., 2023, 145, 1292.; Nat. Catal., 2023, 895.; Nat. Catal., 2023, 6, 1052.]. Metal-molecular sieves have excellent performance in this reaction due to their unique pore structure, rich and adjustable acid sites, and other characteristics, showing great application prospects.
[0003] However, in the process of low-temperature activation and directional conversion of methane, the low methanol and acetic acid yields are still the main bottleneck faced by current supported zeolite catalysts. Constructing highly active metal-zeolite catalysts to increase the yield of oxygen-containing derivatives is still a key scientific problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a Na-modified nanosheet Au-MOR molecular sieve catalyst and a preparation method thereof, as well as an application in the low-temperature oxidation of methane to methanol. The catalyst Au is highly dispersed on the surface of the molecular sieve, and can achieve 100% Au atomic utilization and efficient and highly selective catalytic conversion of methane into methanol.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] On one hand, the present invention provides a Na-modified Au-MOR nanosheet molecular sieve catalyst, wherein the catalyst is represented by the formula Au / Na-MOR, wherein Au and Na are active components, MOR is a carrier, the loading amounts of the active components Au and Na elements in the catalyst are 0.01wt%-2wt% and 0.1wt%-5wt% respectively, and the carrier MOR is composed of cross-growth of nanosheets and has a multi-level pore structure of micropores and mesopores.
[0007] In the above technical solution, further, the loading amount of Au element in the catalyst is 0.1wt%-1wt%; the loading amount of Na element in the catalyst is 0.5wt%-3wt%.
[0008] The order of introduction of active components in the Au / Na-MOR catalyst is to first introduce the base center Na, and then further introduce the active metal component Au.
[0009] Another aspect of the present invention provides a method for preparing the above catalyst, the method comprising the following steps:
[0010] (1) reacting the nanosheet MOR molecular sieve with an ammonium nitrate solution in a water bath at 80-120°C for 6-8 hours, filtering, washing, drying, and then calcining in an air atmosphere to obtain nanosheet H-MOR;
[0011] (2) reacting a soluble salt solution of Na with the nanosheet H-MOR at 50-100° C. for 1-10 h, filtering, washing, drying, and then calcining in an air atmosphere to obtain Na-MOR;
[0012] (3) The soluble salt solution of Au is impregnated on Na-MOR, and after vacuum drying, reduction calcination is performed in a hydrogen atmosphere to obtain the catalyst Au / Na-MOR.
[0013] In the above technical scheme, further, in the step (1), a two-step crystallization method is used to synthesize the sheet MOR, and the specific method is: a silicon source, a template, a sodium source, an aluminum source and water are mixed, and a gel is obtained after stirring for 3 hours. The molar composition of the gel is 2.1 parts of sodium hydroxide: 1 part of aluminum oxide (the raw material is sodium metaaluminate): 17.6 parts of silicon dioxide (silica sol is the silicon source): 11.8 parts of triethylenediamine: 3.8 parts of γ-butyric acid: 264 parts of water. The above gel is placed in a hydrothermal kettle and hydrothermally crystallized under autogenous pressure in an oven at 170°C for 48 hours; after the crystallization is completed, centrifuge to obtain a white powder, dry it at 100°C for 10 hours, and roast it at 550°C for 5 hours in an air atmosphere to obtain a nanosheet MOR (NS) molecular sieve with a multi-level pore structure.
[0014] In the above technical solution, further, in the step (1), the mass ratio of the nanosheet MOR molecular sieve to the ammonium nitrate solution is 1:20;
[0015] The calcination temperature is 300-800°C and the calcination time is 2-10h.
[0016] In the above technical solution, further, in the step (2), the soluble salt solution of Na is one or more of sodium nitrate, sodium chloride, sodium sulfate, sodium acetate, and sodium acetylacetonate.
[0017] In the above technical solution, further, in the step (2), the reaction temperature is 60-80°C and the reaction time is 1-4h.
[0018] In the above technical solution, further, in the step (2), the drying temperature is 60-200°C, preferably 100-120°C;
[0019] The calcination temperature is 350-750° C., preferably 400-600° C., and the calcination time is 1-9 h, preferably 4-6 h.
[0020] In the above technical solution, further, in the step (3), the soluble salt of Au is one or more of chloroauric acid, tetraammine nitrate alloy, and gold chloride.
[0021] In the above technical solution, further, in the step (3), the drying temperature is 60-200°C, preferably 80-100°C;
[0022] The calcination temperature is 300-800° C., preferably 300-500° C., the calcination time is 1-5 h, preferably 2-4 h, and the hydrogen flow rate is 10-100 ml / min, preferably 30-50 ml / min.
[0023] The present invention also provides an application of the above catalyst in the reaction of producing methanol by low-temperature oxidation of methane. The reaction is carried out in an intermittent reactor, with methane, carbon monoxide and oxygen as reaction raw materials, the volume concentrations of methane, carbon monoxide and oxygen are 70%-98%, 1%-20% and 1%-10% respectively, and the reaction raw materials are preferably methane, carbon monoxide and oxygen with volume concentrations of 75%-92%, 5%-18% and 3%-8% respectively; the reaction temperature is 50-250°C, preferably 80-200°C.
[0024] The beneficial effects of the present invention are:
[0025] (1) The Au catalyst of the present invention is highly dispersed on the surface of the molecular sieve, achieving nearly 100% atomic utilization rate.
[0026] (2) The present invention uses nanosheet MOR molecular sieve as a carrier, which has a significant multi-level pore structure, excellent anti-carbon deposition ability and mass transfer and diffusion advantages, which is an important reason why the catalyst has high cycle stability.
[0027] (3) Compared with the reported MOR molecular sieve catalysts, nanosheet MOR has unique acid centers, which can greatly improve the activation efficiency of methane.
[0028] (4) By introducing the base center Na, not only can the distribution of oxygen-containing derivatives on the catalyst be adjusted, but also high selectivity for methanol can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the SEM image of 0.5Au / 1.5Na-MOR(NS) catalyst;
[0030] Figure 2 HADDF-STEM images and element mapping images of 0.5Au / 1.5Na-MOR(NS) catalyst before and after reaction, a is before reaction, b is after reaction;
[0031] Figure 3 HADDF-STEM images and element mapping images of 0.5Au / H-MOR(NS) catalyst before and after reaction, a is before reaction, b is after reaction;
[0032] Figure 4 The stability test results of 0.5Au / 1.5Na-MOR(NS) catalyst are shown in Figure 2.
[0033] Figure 5 The stability test results of 0.5Au / H-MOR(NS) catalyst;
[0034] Figure 6 The stability test results of 0.5Au / H-MOR (commercially available) catalyst;
[0035] Figure 7 These are the results of a stability study of the 0.5Au / Na-MOR (commercially available) catalyst. DETAILED DESCRIPTION
[0036] The following examples are further described in detail. The following examples may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0037] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.
[0038] Example 1
[0039] Preparation of Nanosheet MOR (NS) Molecular Sieve Catalyst:
[0040] (1) A silicon source, a template, a sodium source, an aluminum source and water are mixed and stirred for 3 hours to obtain a gel, wherein the molar composition of the gel is 2.1 parts of sodium hydroxide: 1 part of aluminum oxide (the raw material is sodium aluminate): 17.6 parts of silicon dioxide (silica sol is the silicon source): 11.8 parts of triethylenediamine: 3.8 parts of γ-butyric acid: 264 parts of water;
[0041] (2) placing the above gel into a hydrothermal kettle and hydrothermally crystallizing it in an oven at 170°C under autogenous pressure for 48 hours;
[0042] (3) After the crystallization, the white powder was obtained by centrifugation, dried at 100°C for 10 h, and calcined at 550°C for 5 h in an air atmosphere to obtain a nanosheet MOR (NS) molecular sieve with a multi-level pore structure.
[0043] Embodiment 2-5
[0044] Preparation of Na-MOR catalyst:
[0045] Step A: The nanosheet MOR (NS) molecular sieve prepared in Example 1 was subjected to H exchange, 5 g of the nanosheet MOR (NS) molecular sieve was subjected to surface reaction with 100 g of 1 mol / L ammonium nitrate solution in an 80° C. water bath for 6 h, and then filtered and washed, dried at 100° C. for 10 h, and calcined at 550° C. in an air atmosphere for 4 h to obtain an H-MOR molecular sieve;
[0046] Step B: The H-MOR molecular sieve is subjected to Na exchange, 1 g of H-MOR is subjected to surface reaction with 20 g of sodium nitrate of different concentrations in a water bath at 80° C. for 3 h, and then filtered and washed, dried at 100° C. for 12 h, and calcined at 550° C. for 4 h in an air atmosphere to obtain a Na-MOR catalyst, wherein the loading amount of Na in the base center is 0.5 wt%, 1.5 wt%, 2.5 wt% and 3 wt%, respectively.
[0047] Embodiment 6-9
[0048] Chloroauric acid was dissolved in water and impregnated with the Na-MOR of Examples 2-5 in equal volumes, dried under vacuum at 80°C for 12 h, and stirred at 30 ml / min of H 2 The catalyst was subjected to reduction activation treatment at 400°C for 2 h at a flow rate to obtain Au / Na-MOR(NS) with an Au loading of 0.5 wt%.
[0049] Examples 10-13
[0050] The preparation method of Au / Na-MOR(NS) catalyst is similar to that of Example 7, except that the loading amount of Au is 0.1wt%, 0.3wt%, 0.7wt% and 1wt% respectively.
[0051] Comparative Examples 1-5
[0052] Chloroauric acid was dissolved in water and impregnated with the H-MOR molecular sieve support in equal volumes, dried under vacuum at 80 °C for 12 h, and then heated to 30 ml / min H 2 The catalyst was subjected to reduction activation treatment at 400°C for 2 h at a flow rate to obtain Au / H-MOR catalysts with Au loadings of 0.1 wt%, 0.3 wt%, 0.5 wt%, 0.7 wt% and 1 wt%, respectively.
[0053] Comparative Examples 6-10
[0054] The preparation method of the catalyst is similar to that of Comparative Example 3, except that the carriers are commercially available MOR, H-ZSM-5, Beta, SiO 2 .
[0055] Comparative Examples 11-13
[0056] The preparation method of the catalyst is similar to that of Example 7, except that it is modified with different alkali metals, and the alkali metals are Li, K, and Mg in sequence.
[0057] Figure 1 This is the SEM image of Example 7, which reveals the morphological characteristics of the nanosheet Au / 1.5Na-MOR(NS) through SEM. This result shows that MOR(NS) is composed of stacked flaky nanosheets.
[0058] In order to further reveal the effectiveness and innovation of base center modification, the particle size distribution of Au nanoparticles before and after the reaction of 0.5Au / 1.5Na-MOR(NS) catalyst and 0.5Au / H-MOR(NS) catalyst was investigated by HRTEM. Figure 2 The HADDF-STEM image and element mapping image of the active components of the catalyst 0.5Au / 1.5Na-MOR(NS) before and after the reaction. Figure 3The HADDF-STEM image and element mapping image of the active components of the catalyst 0.5Au / H-MOR(NS) before and after the reaction. The electron microscopy results show that the active components of the 0.5Au / 1.5Na-MOR(NS) catalyst and the 0.5Au / H-MOR(NS) catalyst both exhibit a good dispersion state, indicating the effectiveness of the present invention in preparing highly dispersed metal molecular sieve catalysts. In addition, the Au particles of the 0.5Au / 1.5Na-MOR(NS) catalyst after the reaction did not show agglomeration, while the 0.5Au / H-MOR(NS) catalyst after the reaction showed a more obvious agglomeration phenomenon, indicating that base modification can effectively stabilize the active center Au species, which is also a major innovation of the present invention.
[0059] Test Example 1
[0060] The performance evaluation of the nanosheet Au / Na-MOR (NS) catalyst with different Na contents in Examples 6-9, the evaluation process of the catalyst for low-temperature oxidation of methane to methanol: 25 mg of the catalyst prepared in Example 3 and 10 g of ultrapure water were added to a 50 ml intermittent reactor, and 7 bar of carbon monoxide, 25 bar of methane and 3 bar of oxygen were filled in sequence, and the reaction temperature was 150 ° C. The product was qualitatively and quantitatively detected by liquid nuclear magnetic resonance to achieve comprehensive collection of oxygen-containing derivatives.
[0061] Product selectivity calculation method:
[0062] Methanol selectivity (%) = n 产物中甲醇 / n 反应后所有的含氧衍生物 *100%
[0063] The reaction results are shown in Table 1.
[0064] Table 1
[0065] Serial number catalyst <![CDATA[Methanol yield (umol.g -1 .h -1 )]]> Methanol selectivity (%) Example 6 0.5Au / 0.5Na-MOR(NS) 4233 79 Example 7 0.5Au / 1.5Na-MOR(NS) 5711 90 Example 8 0.5Au / 2.5Na-MOR(NS) 4355 92 Example 9 0.5Au / 3Na-MOR(NS) 3980 95
[0066] From the results in the table, it can be seen that when the Na content is 1.5 wt%, the maximum space-time yield of methanol can be achieved with a methanol selectivity of >90%.
[0067] Test Example 2
[0068] The performance of the nanosheet Au / 1.5Na-MOR (NS) catalysts with different Au contents in Examples 7, 10-13 was evaluated. The reaction conditions were the same as those in Test Example 1. The reaction results are shown in Table 2.
[0069] Table 2
[0070] Serial number catalyst <![CDATA[Methanol yield (umol.g -1 .h -1 )]]> Methanol selectivity (%) Example 10 0.1Au / 1.5Na-MOR(NS) 4026 85 Embodiment 11 0.3Au / 1.5Na-MOR(NS) 4769 88 Example 7 0.5Au / 1.5Na-MOR(NS) 5711 90 Example 12 0.7Au / 1.5Na-MOR(NS) 5289 87 Embodiment 13 1Au / 1.5Na-MOR(NS) 4935 82
[0071] From the results in the table, it can be seen that high selectivity and high space-time yield of methanol can be achieved when the Au content is in the range of 0.1wt%-1wt%.
[0072] Test Example 3
[0073] The performance of the nanosheet Au / H-MOR (NS) catalysts with different Au contents in Comparative Examples 1-5 was evaluated. The reaction conditions were the same as those in Test Example 1. The reaction results are shown in Table 3.
[0074] Table 3
[0075] Serial number catalyst <![CDATA[Methanol yield (umol.g -1 .h -1 )]]> Methanol selectivity (%) Comparative Example 1 0.1Au / H-MOR(NS) 1600 70 Comparative Example 2 0.3Au / H-MOR(NS) 2685 66 Comparative Example 3 0.5Au / H-MOR(NS) 3907 73 Comparative Example 4 0.7Au / H-MOR(NS) 2973 59 Comparative Example 5 1Au / H-MOR(NS) 2768 52
[0076] Test Example 4
[0077] The performance of Au / zeolites catalysts with different molecular sieve supports in Comparative Examples 6-10 was evaluated. The reaction conditions were the same as those in Test Example 1. The reaction results are shown in Table 4.
[0078] Table 4
[0079]
[0080]
[0081] As can be seen from the table, compared with the other four silicon-based carriers, the nanosheet MOR (NS) molecular sieve loaded with Au exhibits higher methanol yield and methanol selectivity.
[0082] Test Example 5
[0083] The performance of the 0.5Au / 1.2M-MOR(NS) catalysts modified with different alkali metals in Comparative Examples 11-13 was evaluated. The reaction conditions were the same as those in Test Example 1. The reaction results are shown in Table 5.
[0084] Table 5
[0085] Serial number catalyst <![CDATA[Methanol yield (umol.g -1 .h -1 )]]> Methanol selectivity (%) Example 7 0.5Au / 1.5Na-MOR(NS) 5711 90 Comparative Example 11 0.5Au / 1.5Li-MOR(NS) 4633 79 Comparative Example 12 0.5Au / 1.5K-MOR(NS) 4219 75 Comparative Example 13 0.5Au / 1.5Mg-MOR(NS) 1126 70
[0086] According to the above results, only the Na-modified molecular sieve Au / M-MOR(NS) catalyst can achieve high selectivity and high space-time yield of methanol.
[0087] Test Example 6
[0088] The catalytic performance of 0.5Au / 1.5Na-MOR(NS) was investigated at different calcination temperatures. The reaction temperature ranged from 80 to 200°C. The other reaction conditions were the same as those in Test Example 1.
[0089] Table 6
[0090] Reaction temperature (oC) <![CDATA[Methanol yield (umol.g -1 .h -1 )]]> Methanol selectivity (%) 80 1243 78 100 2785 87 120 4388 88 150 5711 90 180 4972 69 200 2861 65
[0091] The catalyst provided by the present invention can produce the target product acetaldehyde under the reaction condition of 80-200°C, the preferred reaction temperature is 120-180°C, and the optimal temperature is 150°C.
[0092] Test Example 7
[0093] In order to further highlight the superiority of the present invention, the cyclic stability of the catalyst 0.5Au / 1.5Na-MOR(NS) was investigated, and the stability of the catalyst 0.5Au / H-MOR(NS) without Na modification was compared. Figure 4 , 5 This result indicates that the Na-modified catalyst can not only achieve high methanol yield and high selectivity, but also exhibit outstanding reaction cycle stability.
[0094] To further demonstrate the uniqueness of the present invention, we further compared commercially available MOR and Na-MOR (commercially available) that underwent Na exchange, and the specific preparation process was similar to that of Example 2. The corresponding catalytic performance was examined, further highlighting the superiority of the catalyst of the present invention. Figure 6 , 7 The results show that for commercially available MOR, whether or not an alkali metal center is introduced for modification, the cyclic stability of the reaction is not further improved, indicating the uniqueness of the present invention.
[0095] In summary, the nanosheet molecular sieve catalyst Au / Na-MOR modified with alkaline center Na in the present invention can be used for the low-temperature oxidation of methane to methanol. The catalyst prepared by this strategy has the advantages of good activity, high methanol selectivity, high Au atom utilization rate, and good reaction cycle stability.
[0096] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A Na-modified Au-MOR nanosheet molecular sieve catalyst, characterized in that: The catalyst is represented by the formula Au / Na-MOR, wherein Au and Na are active components, MOR is a carrier, the loading amounts of the active components Au and Na elements in the catalyst are 0.01wt%-2wt% and 0.1wt%-5wt% respectively, and the carrier MOR is composed of cross-growth of nanosheets and has a multi-level pore structure of micropores and mesopores.
2. The catalyst according to claim 1, characterized in that: The loading amount of Au element in the catalyst is 0.1wt%-1wt%; the loading amount of Na element in the catalyst is 0.5wt%-3wt%.
3. A method for preparing the catalyst according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: (1) reacting the nanosheet MOR molecular sieve with an ammonium nitrate solution in a water bath at 80-120° C. for 6-8 hours, filtering, washing, drying, and then calcining in an air atmosphere to obtain nanosheet H-MOR; (2) reacting a soluble salt solution of Na with the nanosheet H-MOR at 50-100° C. for 1-10 h, filtering, washing, drying, and then calcining in an air atmosphere to obtain Na-MOR; (3) The soluble salt solution of Au is impregnated on Na-MOR, and after vacuum drying, reduction calcination is performed in a hydrogen atmosphere to obtain the catalyst Au / Na-MOR.
4. The preparation method according to claim 3, characterized in that: In the step (1), the mass ratio of the nanosheet MOR molecular sieve to the ammonium nitrate solution is 1:20; The calcination temperature is 300-800°C and the calcination time is 2-10h.
5. The preparation method according to claim 3, characterized in that: In the step (2), the soluble salt solution of Na is one or more of sodium nitrate, sodium chloride, sodium sulfate, sodium acetate, and sodium acetylacetonate.
6. The preparation method according to claim 3, characterized in that: In the step (2), the reaction temperature is 60-80° C. and the reaction time is 1-4 h.
7. The preparation method according to claim 3, characterized in that: In the step (2), the drying temperature is 60-200°C; The calcination temperature is 350-750°C, and the calcination time is 1-9h.
8. The preparation method according to claim 3, characterized in that: In the step (3), the soluble salt of Au is one or more of chloroauric acid, tetraammine nitrate alloy, and gold chloride.
9. The preparation method according to claim 3, characterized in that: In the step (3), the drying temperature is 60-200°C; The calcination temperature is 300-800°C, the calcination time is 1-5h, and the hydrogen flow rate is 10-100ml / min.
10. Use of the catalyst according to any one of claims 1 to 2 in the reaction of producing methanol by low-temperature oxidation of methane, characterized in that: The reaction is carried out in an intermittent reactor, with methane, carbon monoxide and oxygen as reaction raw materials, the volume concentrations of methane, carbon monoxide and oxygen being 70%-98%, 1%-20% and 1%-10% respectively, and the reaction raw materials are preferably methane, carbon monoxide and oxygen with volume concentrations of 75%-92%, 5%-18% and 3%-8% respectively; the reaction temperature is 50-250°C.
Citation Information
Patent Citations
Catalyst for preparing methane by low-temperature oxidization of methane and preparation method and application thereof
CN101875016A
Catalyst for reaction for preparing 1,3-butadiene from ethanol, preparation and applications thereof
CN111217656A
Synthetic method of mordenite molecular sieve with sheet staggered structure and molecular sieve
CN114804140A
Artificial intelligence-based companion animal management device and system therefor
KR1020240084592A